2016
DOI: 10.3847/0004-637x/831/1/88
|View full text |Cite
|
Sign up to set email alerts
|

Spitzer Irac Observations of Ir Excess in Holmberg Ix X-1: A Circumbinary Disk or a Variable Jet?

Abstract: We present Spitzer Infrared Array Camera (IRAC) photometric observations of the Ultra-luminous X-ray Source (ULX, X-1) in Holmberg IX. We construct a spectral energy distribution (SED) for Holmberg IX X-1 based on published optical, UV and X-ray data combined with the IR data from this analysis. We modeled the X-ray and optical data with disk and stellar models, however we find a clear IR excess in the ULX SED that cannot be explained by fits or extrapolations of any of these models. Instead, further analysis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Observational evidence for mid-infrared emission from a dusty CB disk illuminated by the compact X-ray source has been found in several X-ray binaries, such as the Galactic BH candidates GRS 1915+105 (Rahoui et al 2010), A0620−00 and XTE J1118+480 (Muno & Mauerhan 2006). Among ULXs, a CB disk was proposed for Holmberg IX X-1 (Dudik et al 2016) and Holmberg II X-1 (Lau et al 2017). A CB disk fed by outflows through the L2 point is also likely to be present in SS 433, based on optical spectroscopic studies of its stationary Hα, Brγ, Paschen, and He I emission lines (Blundell et al 2008;Perez & Blundell 2009, 2010Bowler 2013).…”
Section: Implications For the System Parametersmentioning
confidence: 99%
“…Observational evidence for mid-infrared emission from a dusty CB disk illuminated by the compact X-ray source has been found in several X-ray binaries, such as the Galactic BH candidates GRS 1915+105 (Rahoui et al 2010), A0620−00 and XTE J1118+480 (Muno & Mauerhan 2006). Among ULXs, a CB disk was proposed for Holmberg IX X-1 (Dudik et al 2016) and Holmberg II X-1 (Lau et al 2017). A CB disk fed by outflows through the L2 point is also likely to be present in SS 433, based on optical spectroscopic studies of its stationary Hα, Brγ, Paschen, and He I emission lines (Blundell et al 2008;Perez & Blundell 2009, 2010Bowler 2013).…”
Section: Implications For the System Parametersmentioning
confidence: 99%
“…1-σ flux uncertainties are provided in the parentheses. (Berghea et al 2010a;Dudik et al 2016). Possible origins include heated dust shells like those detected around red supergiants, circumbinary dust disks, jets, and/or free-free emission from accretion disk winds.…”
Section: Nature Of the Mid-ir Emissionmentioning
confidence: 99%
“…Only a few observational studies of the mid-IR emission from ULXs exist (Berghea et al 2010a(Berghea et al , 2010bDudik et al 2016). Berghea et al (2010aBerghea et al ( , 2010b present mid-IR photometry of the well-studied Holmberg II X-1 (hereafter referred to as X-1; Pakull & Mirioni 2002;Lehmann et al 2005;Tao et al 2012;Walton et al 2015) and analyze its full radio to X-ray spectral energy distribution (SED).…”
Section: Introductionmentioning
confidence: 99%
“…Heil et al 2009). For example, Dudik et al (2016) combined multi-wavelength IR to Xray observations of the ULX Holmberg IX X-1 taken over 5 years and concluded that the origin of its mid-IR emission is either circumstellar dust or a variable jet. The uncertain origin of the mid-IR emission from Ho IX X-1, which exhibits X-ray variations by factors of 3-4 on day to year timescales (Vierdayanti et al 2010;Walton et al 2017), was attributed to difficulties in generating a good fit to the multi-wavelength, multi-epoch observations.…”
mentioning
confidence: 99%